Heat Capacity of 1D Molecular Chains; Journal of Low Temperature Physics; Vol. 187, iss. 1 - Bagatskii M. I. Michail Ivanovich; Barabashko M. S. Maksim Sergeevich; Sumarokov V. V. Vladimir Victorovich; Jezowski A. Andrzej; Stachowiak P. Petro (2017, 2017)
Title screen